Validation of at least 1 mm as cut-off for resection margins for pancreatic adenocarcinoma of the body and tail - Hank, Thomas; Hinz, Ulf; Tarantino, Ignazio; Kaiser, Jörg; Niesen, Willem; Bergmann, Frank; Hackert, Thilo; Büchler, Markus W.; Strobel, Oliver (The British journal of surgery, 2018)
Background The definition of resection margin (R) status in pancreatic cancer is under debate. Although a margin of at least 1 mm is an independent predictor of survival after resection for pancreatic head cancer, its relevance to pancreatic body and tail cancers remains unclear. This study aimed to validate R status based on a 1-mm tumour-free margin as a prognostic factor for resected adenocarcinoma involving the pancreatic body and tail. Methods Patients who underwent distal or total pancreatectomy for adenocarcinomas of the pancreatic body and tail between January 2006 and December 2014 were identified from a prospective database. Resection margins were evaluated using a predefined cut-off of 1 mm. Rates of R0, R1 with invasion within 1 mm of the margin (R1 less than 1 mm), and R1 with direct invasion of the resection margin (R1 direct) were determined, and overall survival in each group assessed by Kaplan-Meier analysis. Univariable and multivariable Cox regression analyses were performed to identify predictors of survival. Results R0 resection was achieved in 107 (23·5 per cent) and R1 in 348 (76·5 per cent) of 455 patients. Among R1 resections, invasion within 1 mm of the margin was found in 104 (22·9 per cent) and direct invasion in 244 (53·6 per cent). The R0 rate was 28·9 per cent after distal and 18·6 per cent after total pancreatectomy. In the total cohort, median survival times for patients with R0, R1 (less than 1 mm) and R1 (direct) status were 62·4, 24·6 and 17·2 months respectively, with 5-year survival rates of 52·6, 16·8 and 13·0 per cent (P < 0·001). In patients who received adjuvant chemotherapy, respective median survival times were 68·6, 32·8 and 21·4 months, with 5-year survival rates of 56, 22 and 16·0 per cent (P < 0·001). In multivariable analysis, R status was independently associated with survival. Conclusion A cut-off of at least 1 mm for evaluation of resection margins is an independent determinant of survival after resection of adenocarcinomas of the pancreatic body and tail.